Burnout, Work Addiction and Stress-Related Growth Among Emergency Physicians and Residents: A Comparative Study - Raluca Mihaela Tat; Adela Golea; Gabriela Vancu; Mihai-Bujor Grecu; Monica Puticiu; Andrei Hermenean; Luciana Teodora Rotaru; Mihai Alexandru Butoi; Mihaela Corlade-Andrei; Diana Cimpoesu (Behavioral Sciences, 2025)
The field of emergency medicine (EM) is a high-stress medical specialty. We aim to comparatively investigate burnout, work addiction, and stress-related growth between EM physicians and EM residents. Our sample consists of 117 EM professionals, 41 physicians and 76 residents, from 5 out of the 12 EM county departments in Romania that run residency programs. Methods: An online survey was sent to 461 EM professionals (170 physicians and 291 residents), with a response rate of 25.4%. The survey comprised two sections: the first focused on sociodemographic and professional data, with the second consisting of six validated assessment instruments: the Oldenburg Burnout Inventory, Dutch Work Addiction Scale—short version, Stress-Related Growth Scale, Responsive Distress Scale, Self-Discipline Scale, and Zuckerman–Kuhlman Personality Questionnaire. Both EM physicians and residents reported moderate to high levels of burnout, disengagement, and exhaustion, but there was no significant difference between them. However, physicians exhibited significantly higher levels of work addiction, excessive work, compulsive work, and stress-related growth. No significant differences were found in compulsive work behaviors. Conclusions: Burnout levels are comparable between EM physicians and residents. However, physicians demonstrate higher work addiction but also higher stress-related growth. Personality variables and sleep duration appear to be more influential in predicting burnout than in work addiction or stress-related growth.